Socioeconomic study for the wealth of marine shrimp in the territorial sea of Iraq - Ali, Malik H.; Ahmed, Huda K. (Iraqi Journal of Aquaculture, 2021)
The present study was designed to investigate the contribution of shrimp fisheries and the related activities to the economy Iraq. For this purpose a socioeconomic information and data were collected for one year (2014) period. Three marine penaeid shrimps were constituted the majority of shrimp fisheries in Iraqi marine water, these are: Penaeus semisulcatus, Metapenaeus affinis and Parapenaopsis styliferus. University of Basrah institutes basically the Marine Science Center, apparently is the marine institute implemented researches and studies on shrimp landing have been recorded at Al Nasser fishing Society of the Basrah / Faw city. On the other side, the study concluded that any real and accurate data on shrimp landing can be only obtained from fisherman on the fishing boat of the field. In fact the marine fishing area of Iraq is very limited and the investigation shows that there are nearly 150- 250 fishing boats, 450 – 600 fisher man and 70 – 110 fishmonger contributing in the shrimp sector. However, their economy doesn’t restricted on shrimp, but, usually cornering other fish resources. The results revealed that, the increasing of anthropological activities, overfishing, high by catch, the degradation of natural habitats such as coastal mudflats and Marshes and pollution are the basic factors reducing the shrimp stocks. For best monitoring and data collection of the shrimp resources, a networking information and data collection system is provided.